2013
DOI: 10.5194/acp-13-611-2013
|View full text |Cite
|
Sign up to set email alerts
|

The spring 2011 final stratospheric warming above Eureka: anomalous dynamics and chemistry

Abstract: Abstract. In spring 2011, the Arctic polar vortex was stronger than in any other year on record. As the polar vortex started to break up in April, ozone and NO 2 columns were measured with UV-visible spectrometers above the Polar Environment Atmospheric Research Laboratory (PEARL) in Eureka, Canada (80.05 • N, 86.42 • W) using the differential optical absorption spectroscopy (DOAS) technique. These ground-based column measurements were complemented by Ozone Monitoring Instrument (OMI) and Optical Spectrograph … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The four longer wavelengths are used for the ozone retrieval. The TCO is calculated by analyzing the relative intensities at these different wavelengths using the Bass and Paur (1985) ozone cross section.…”
Section: Brewermentioning
confidence: 99%
See 1 more Smart Citation
“…The four longer wavelengths are used for the ozone retrieval. The TCO is calculated by analyzing the relative intensities at these different wavelengths using the Bass and Paur (1985) ozone cross section.…”
Section: Brewermentioning
confidence: 99%
“…These results (at Eureka) are better than the high-latitude agreement reported by Hendrick et al (2011), who found that SAOZ TCO (1990TCO ( -2008 was systematically lower than Brewer TCO at Sodankylä (67 • N, 27 • E) by 3 %-4 %, with the largest discrepancies in the spring and fall. Hendrick et al (2011) suggested that this bias was due to the temperature dependence (Kerr, 2002;Kerr et al, 1988;Scarnato et al, 2009;Van Roozendael et al, 1998;Zhao et al, 2016b) and uncertainty in the ozone cross section (Bass and Paur, 1985) used in Brewer measurements. The agreement between the UT-GBS, SAOZ, and Brewer in Adams et al (2012) (and this study) is notable given the challenges of taking ZS-DOAS measurements at 80 • N, particularly in the summer when measurements within the NDACC-recommended SZA range are not available.…”
Section: Weather Impacts On Tco Accuracymentioning
confidence: 99%
“…Satellite-based estimates of NO 2 columns have been widely used in studies of atmospheric chemistry, air quality, and climate (greenhouse gas trends and lifetimes), and in the evaluation of chemistry transport models (CTMs). In the stratosphere, satellite-based NO 2 observations have been used to study factors influencing ozone loss and recovery [e.g., Adams et al, 2013] as well as long-term trends in stratospheric composition [e.g., Dirksen et al, 2011, Hendrick et al, 2012. In the troposphere, satellite NO 2 records show the sources [van der A et al, 2008;Lin et al, 2010;Ghude et al, 2013;Mebust et al, 2011;Mebust and Cohen, 2013], spatial patterns [Martin et al, 2003;Toenges-Schuller et al, 2006;Russell et al, 2010;Hilboll et al, 2013a], and trends of NO x emissions [Richter et al, 2005;Kim et al, 2006;Zhang et al, 2007;Boersma et al, 2008;McLinden et al, 2012;de Wildt et al, 2012;Russell et al, 2012;Duncan et al, 2013;Streets et al, 2013;Vinken et al, 2014], NO x lifetimes [Schaub et al, 2007;Lamsal et al, 2010;Beirle et al, 2011], and the impact of population and economic activity on NO x emissions .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, vertical profiles of MERRA-2 ozone (Wargan et al, 2017), temperature, pressure, and scaled potential vorticity (sPV) over Eureka were computed using the Jet and Tropopause Products for Analysis and Characterization (JETPAC) package described by Manney et al (2011. The sPV is potential vorticity scaled in "vorticity units" to give a similar range of values at each level, which can be used to identify the location of the polar vortex (Dunkerton and Delisi, 1986;Manney et al, 1994;Adams et al, 2013;Zhao et al, 2017). The profile data are on 72 model levels with 3-hour temporal resolution and approximately 1-km vertical spacing near the tropopause.…”
Section: Merra-2mentioning
confidence: 99%